Gender and colonialism : a history of Kaoko in north-western Namibia, 1870s-1950s - Rizzo, Lorena (Basel Namibia studies series, 2012)
This book deals with colonialism on a Namibian periphery and considers both the German colonial period as well as South African rule in the country. The marginality of the Kaoko region within this colonial topography of power is analysed as a dynamic and fractured feature where power relations and constellations remained highly contested. The dynamics of gender within a regional society constituted of men and women, African and European, receive special attention within frameworks engaging with colonial photography, oral histories and gendered visions.